2018
DOI: 10.22201/ib.20078706e.2018.2.2016
|View full text |Cite
|
Sign up to set email alerts
|

La estacionalidad climática no afecta la fenología de murciélagos cavernícolas con dieta omnívora

Abstract: ResumenLa fenología de los animales es influenciada de manera importante por la estacionalidad climática que promueve cambios en la abundancia de recursos alimenticios. Especies con dieta omnívora podrían no ser afectadas por la estacionalidad al poder utilizar diferentes recursos disponibles en el tiempo. Para probar esta hipótesis, describimos la fenología reproductiva de 3 especies de murciélagos cavernícolas con diferentes hábitos alimenticios en un bosque templado. Los murciélagos fueron capturados mensua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…This synchrony has been recorded in both Pipistrellus nathusii and Nictalus noctule, where an increase in abundance co-occurs with pup independence not only in forested areas in the Americas, but also in farmlands in Europe (Racey and Entwistle 2000;Klingbeil and Willig 2010;Heim et al 2016). We do not have information on the timing of breeding bats in our study site; however, pregnant females of Myotis velifer have been reported at the end of the dry season in temperate forests close to Morelia (Ferreyra-García et al 2018). Nursing and pregnant females of frugivorous Dermanura azteca and Artibeus lituratus have also been captured in Morelia city in the mid-dry season (Chavez-Estrada Pers.…”
Section: Discussionsupporting
confidence: 51%
“…This synchrony has been recorded in both Pipistrellus nathusii and Nictalus noctule, where an increase in abundance co-occurs with pup independence not only in forested areas in the Americas, but also in farmlands in Europe (Racey and Entwistle 2000;Klingbeil and Willig 2010;Heim et al 2016). We do not have information on the timing of breeding bats in our study site; however, pregnant females of Myotis velifer have been reported at the end of the dry season in temperate forests close to Morelia (Ferreyra-García et al 2018). Nursing and pregnant females of frugivorous Dermanura azteca and Artibeus lituratus have also been captured in Morelia city in the mid-dry season (Chavez-Estrada Pers.…”
Section: Discussionsupporting
confidence: 51%